Cervix cancer brachytherapy: time for changes? - Serkies, Krystyna; Wejs-Maternik, Julianna; Tarnawska, Zofia; Jassem, Jacek (Contemporary Oncology/Współczesna Onkologia, 2006)
Radiotherapy, currently administered together with cisplatin, is beside surgery the main method of most invasive cervical cancer treatment. This modality consists of external beam irradiation and brachytherapy. In the aim of treatment optimization several methods including conformal techniques have been attempted. Most frequent application of image-based three-dimensional treatment planning systems (3D) allows for dose-volume histograms, which describe the relationship between volume dose and local control probability or the risk of side effects. Here we present recently reported American and European guidelines and recommendations on the use of 3D brachytherapy in cervical cancer patients.